Research progress on psychological nursing of patients with cancer pain (老年癌痛患者心理护理研究进展) - YU Zijun (于紫君); YANG Shuang (杨爽) (中西医结合护理)
Cancer-related pain, is one of the most common and troublesome symptoms affecting quality of life and mental health of patients with cancer. Psychotherapy is a treatment intervention used to help individuals manage and overcome a range of emotional, psychological, and behavioral issues. This paper reviewed studies on psychological nursing of patients with cancer pain in perspectives of pain awareness, factors influencing the emotional disorders and related psychological nursing interventions, in order to provide reference for pain relief and improvement of mental health and quality of life. (癌痛是癌症患者的常见症状, 不仅影响患者生活质量, 同时也会给给患者带来巨大的心理负担。心理疗法主要针对癌痛患者的情感、认知和行为等方面的问题。本研究就疼痛的认识、癌痛情志障碍影响因素以及相关心理护理措施进行综述, 旨在为改善癌痛患者心理状态、减轻疼痛和提高生活质量提供参考。)